Acute bilateral emphysematous pyelonephritis successfully managed by medical therapy alone: A case report and review of the literature - Flores, Guillermo (BioMed Central, 2002)
BACKGROUND: Bilateral emphysematous pyelonephritis is a life threatening condition usually occurring in diabetics. Management of this condition has traditionally been aggressive and surgery is considered mandatory. However, this is itself a hazardous intervention in a septic, unstable patient with circulatory or liver failure. When bilateral disease is present, the need for long-term dialysis is obviously unavoidable. CASE PRESENTATION: We herein report one of the few cases of bilateral emphysematous pyelonephritis successfully managed by non-surgical treatment.